PENGEMBANGAN PERILAKU HIDUP BERSIH DAN SEHAT PADA SISWA SMK KESEHATAN CITRA MEDIKA GROUP - Hikmah, Nur; Cahyaningrum, Nopita (Politeknik Kesehatan Kemenkes Bengkulu, 2020)
The clean and healthy behavior of adolescents is very low, even though adolescents are a very important stage of child development considering that adolescents enter growth sports or rapid development, apart from puberty. In this phase there is physical growth accompanied by mental cognitive development, psychological development and reproduction, which regulates the function of sexuality, so it is very important to implement clean and healthy behavior. The purpose of this study was to analyze the development of clean and healthy life behaviors among students of the Citra Medika Group Health Vocational School. The research method used in this study is an exploratory survey, with a sample size of 288 students with a sampling technique proportionate stratifired random sampling. The results showed that the clean and healthy lifestyle of the students was good as much as 77.1% with indicators of good hand washing behavior with soap as much as 91.8%, behavior using good healthy latrines as much as 97.6%, behavior doing sports or high physical activity. 53.4%, good mosquito larva eradication behavior as much as 63.7%, smoking behavior mostly do not smoke as much as 99.4%, all students do not consume drugs or as much as 100%, behavior throwing garbage in its place is good as much as 98.4% , behavior measuring body weight and height irregular as much as 73.8% and behavior of consuming good fruit and vegetables as much as 57.6%. Based on the results of the study, it can be seen that most of the students have a good clean and healthy lifestyle, this is because all students have gained good knowledge as well.